The Silly Gooses - Pilkey, Dav, 1966- (New York : Blue Sky Press, 1997)
Mr. Goose and Miss Goose, who are always doing very silly things, become the Silly Gooses when they marry and start a family.
School Library Journal.
Bulletin (Center for Children's books).
L.A. Recommended Foreign Language.
2.8
K-3
Keywords: Geese -- Fiction; Humorous stories; Geese -- Fiction; Humorous fiction; Geese -- Fiction; Humorous stories